Understanding the purchasing behaviors of halal cosmetics of teenagers in Indonesia using the theory of planned behavior and theory of consumption value - Huriah, Titih; Permana, Iman; Octavia, Mega; Abdul Hamid, Siti Hazariah (Sanglah General Hospital, 2022)
Introduction: Public awareness of halal lifestyles is increasing. This understanding concerns food and beverage and other halal aspects such as halal tourism, household needs and halal cosmetics. Indonesia is the country with the largest Muslim population in the world. However, the general public, especially teenagers, does not understand the concept of halal cosmetics, which currently prefers other cosmetic products whose halal identity is not yet clear. The willingness and intention to use halal cosmetics remain low. This research aims to determine the factors affecting the use of halal cosmetics in Indonesian students. Methods: The study design was a descriptive study with a cross-sectional approach. This study combined the Theory of Planned Behavior and the Theory of Consumption Value (TCV) to identify factors affecting halal cosmetics in Indonesian students. This research employed a structured online survey, and 934 Muslim students aged 17 to 30 years old. The analysis process used Partial Least Square-Structural Equation Modelling (PLS-SEM). Results: The results showed that three of the 11 hypotheses were not proved. There was a significant relationship between intention, conditional value, epistemic value, emotional value, and halal cosmetics, with an R square value of 0.762. Conclusion: Four factors affect the use of halal cosmetics, 76.2%, while other factors outside the model cause the additional 23.8%.